Calcium superphosphate as an inorganic stabilizer for modified-Fenton treatment of diesel-contaminated soil with two different exogenous iron sources. (20th April 2021) - Qin, Jiaolong; Zhang, Shuqi; Zhu, Yitong; Radian, Adi; Long, Mingce
Abstract: Catalyzed hydrogen peroxide propagation (CHP) processes are widely applied for the remediation of petroleum hydrocarbon contaminated soils, but greatly limited by the rapid decomposition of H2 O2 . Although phosphate stabilizer can extend the lifetime of H2 O2 in the soil systems, it is unclear about the effect of stabilizers on the processes with different exogenous iron species that are frequently added to accelerate the Fenton-like reactions. Herein, calcium superphosphate (CAP) was used as a H2 O2 stabilizer in the modified-Fenton treatment of the diesel spiked soil with two exogenous iron species, a citrate chelated ferric complex (IC) and an iron mineral (γ-Fe2 O3 immobilizing on montmorillonite, IB). A ratio of CAP to soil (RCS) at 1/10 can retain 49% of H2 O2 within 24 h in the soil. The diesel removal efficiency in the IC based process reached 70% at 10 h after adding 480 mM H2 O2 when IC and RCS were 90 mM and 1/10, which is much higher than that in the IB based process. In the latter system, only 23% diesel removal can be achieved at 48 h after adding the same dosage of H2 O2 and CAP. This can be attributed to the higher concentration of hydroxyl radicals produced in the former process. The O2 detection showed that CAP can effectively retard H2 O2 decomposition into O2 in the both processes. A relatively high dosage of CAP should be applied in the IC process to retain H2 O2 and extend ·OH production for diesel degradation, while a relatively low dosage of CAP can promote the diesel removal by altering the O2 production through a superoxide radical mediated pathway. Graphical abstract: Image 1 Highlights: Calcium superphosphate (CAP) inhibited the invalid decomposition of H2 O2 in soil. Effects of CAP on the remediation of diesel-polluted soil varied with iron sources. High dosages of CAP are required for diesel removal in chelated-Fe(III) processes. CAP promotes diesel removal in exogenous iron minerals modified Fenton treatment. CAP inhibits hydroxyl radical generation and alters oxygen production pathways.